Highly Dynamic Yet Stable Polyketimine Networks with Closed-Loop Recyclability and Topological Programmability - Xiao Liu; Ben He; Yi Sheng; Cheng Liu; Hong Wan; Dongyu Chen; Bo Yang; Hongfeng Mu; Qian Zhao; Kaichen Xu; Zhibo Li; Tao Xie; et al. (Journal of the American Chemical Society, 2026)
Abstract Closed-loop recycling via depolymerization has emerged as a promising strategy to mitigate plastic pollution. Ideal recyclable polymer networks should feature highly dynamic bonds that depolymerize efficiently into monomers/oligomers. However, this intrinsic bond lability inevitably introduces a critical trade-off, as it typically undermines the material’s stability. In this work, we design a polyketimine network that can be closed-loop recycled under mild conditions, without the need for consumable reagents or catalysts, while retaining robust mechanical properties during use. At the molecular level, hindered ketimine bonds remain sufficiently labile to depolymerize back to the designed oligomers, due to the steric hindrance from the ketone and amine reactants. At the network level, however, hydrophobic phases block water ingress, effectively “locking” the network and preserving mechanical performance even under harsh conditions (85 °C, 85% relative humidity, 48 h). When recycling is desired, a compatible organic solvent disrupts these hydrophobic phases, allowing water to penetrate the network and trigger depolymerization. Consequently, depolymerization and repolymerization cycles can be conducted using only easily recoverable water and solvents under mild conditions. By leveraging this dynamic chemistry, the synthesized polymers can be disassembled and reassembled into diverse network topologies, corresponding to a Young’s modulus that spans 6 orders of magnitude. Our work demonstrates that intrinsically labile dynamic bonds can be harnessed to build stable materials with tunable properties, offering a versatile platform for next-generation closed-loop recyclable polymers.